Embedded multiplexed polymer optical fiber sensor for esophageal manometry - Kalli, Kyriacos; Missinne, Jeroen; Bosman, Erwin; Van Hoe, Bram; Van Steenberge, Geert; Van Daele, Peter P.; Zhang, Wei; Johnson, Ian P.; Sugden, Kate; Webb, David (My University, 2011)
There is a growing interest for esophageal measurements which can provide important and reliable data when diagnosing the motor function of the sphincters and the esophageal body. Biocompatibility, sensing resolution and the comfort of the patient are key parameters for manometric sensing systems. A new sensing approach which could fulfill all these needs is presented in this paper consisting of an embedded polymer fiber sensor, based on multiplexed fiber Bragg gratings. A response to a radial pressure almost 6 times that of a comparable silica fiber based sensor is obtained.
Keywords: Biocompatibility; Multiplexing; Silica